PROCEDURES OF TRANSLATING SONG LYRICS INTO INDONESIAN OF “THINGS WILL GET BETTER” BY AGNES MONICA - Riki Irawan; Mundriyah Mundriyah (PROJECT (Professional Journal of English Education), 2022)
This study concentrated on investigating the use of the translation procedure of the translated lyrics. The objectives of the research were to find out the translation procedure used to translate song lyrics by Agnes Monica "things will get better" and the moral value in her album Agnezmo. This is a qualitative study. Data examination was paralleling the authentic language and the translated lyrics type to investigate the most used of translation procedure. The outcomes of the research displayed that there were 23 data of the translated lyrics and 8 translation procedures established in this study. Literal translation procedure was the highest often used with a total of nine, shadowed by Established equivalent with a total of four. Several other translation procedures were used temperately like linguistic compression with a total of three. The rest procedures used in small levels with a total of one in each, like modulation, amplification, linguistic amplification, and particularization. While the moral value of the song was an effort will not betray the results, but mutual trust and forgiveness of each other in a relationship is the key or way so that the relationship will go on better. Keywords:  Translating Procedures, Lyric, Song, Moral Value